Think Twice Before You 'Boo' Your Sports Competitor - Irma Kurniawan (Opticon1826, 2009)
Next time you watch a heavy weight lifting tournament, tell the person next to you not to boo the person that he doesn’t want to win. A study recently published shows that modifying someone’s arousal level can influence their force production. Arousal refers to a physiological or psychological state of excitability, which in this study was enhanced by eliciting either negative or positive moods. The research was led by Liane Schmidt and Mathias Pessiglione and aimed to investigate if motivation to exert vigour can be changed by changing the person’s mood. The study was inspired by major sporting events such as the Olympics, where cheering spectators and cameras follow the athlete’s performance closely. Activities such as the ones involving physical force (e.g., heavy weight lifting) can be influenced by particular surrounding environment. The research team asked if having a positive, neutral, or negative mood changes maximal force production. During the investigation, participants were asked to squeeze a hand device as hard as they could to mimic the challenge of a heavy weight-lifting competition. To change their mood, participants were presented with emotional and neutral pictures taken from a widely-validated database of images, the International Affective Picture System (IAPS; Lang, Bradley & Cuthbert, 2005). These pictures were presented for several seconds right before participants voluntarily produced their maximal force. The images were either negative (a picture of a gun), neutral (a picture of a piece of furniture), or positive (a picture of a baby smiling). Presenting pictures in this manner is a robust way of eliciting mood changes.
Keywords: competitive sport; emotional states; force production